FACTORS AFFECTING CONSUMER RESISTANCE TOWARD SMART VOICE ASSISTANTS USAGE FOR ONLINE SHOPPING: THE ROLE OF PRIVACY CYNICISM AND PERCEIVED CREEPINESS (Third Sector Social Economic Review, 2025)
AAs a result of advancements in natural language processing and voice technology, voice assistants have become significant artificial intelligence tools shaping consumer behavior. However, privacy concerns have been the most important issue that hinders the adoption of Smart Voice Assistants (SVAs).  So far, many studies have sought to explain the adoption behavior patterns of SVAs, and limited research has taken resistance factors in the context of online shopping into consideration. Thus, this study addresses the factors affecting consumer resistance toward SVA usage for online shopping behavior. Privacy cynicism was used to explain the privacy concerns of consumers and the effects of privacy cynicism and perceived creepiness on resistance intention towards SVAs were examined. A convenience sample method is employed and the online survey method is used to reach the sample consisting of consumers using SVAs aged 18 and above. A partial least squares structural equation (PLS-SEM) is carried out to process 252 surveys. The results showed that privacy cynicism influences perceived creepiness positively and perceived creepiness has a positive influence on resistance intention. While the direct effect of privacy cynicism on resistance intention is significant, it turns positive and significant through the perceived creepiness. Recommendations were offered to the practitioners and scholars following the findings.
Keywords: Privacy cynicism; Perceived creepiness; Voice assistants; Consumer resistance; Technology adoption